2014
DOI: 10.1007/s10800-014-0722-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of dendritic growth of zinc crystals on the edges of steel sheet

Abstract: In this paper, the formation of zinc dendrites at the strip edge of an industrial electrogalvanizing line was studied. For that purpose, a rotating washer electrode was designed to reproduce the hydrodynamic conditions and the current density distribution found in the industrial process. Polarization curves were recorded at different rotation speeds in order to investigate the electrokinetic behavior of the cathodic process. The induction time for dendritic growth was estimated for different overpotential valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Earlier results in the literature showed that zinc dendritic growth preferentially occurs at the edges and along the boundaries of the electrode where the current density is higher compared to the center. 54,55 Therefore, the morphologies of the zinc deposits obtained at the edge and at the center region of the deposits in the electrolytes of 1.5 M ZnO/IL, 0.4 M Zn(TfO) 2 /IL and (0.4 M Zn(TfO) 2 + 1.5 M ZnO)/IL at −1.8 V for 2 h, respectively, were investigated by scanning electron microscopy (SEM). The images are shown in Fig.…”
Section: Morphology Of the Zinc Depositsmentioning
confidence: 99%
“…Earlier results in the literature showed that zinc dendritic growth preferentially occurs at the edges and along the boundaries of the electrode where the current density is higher compared to the center. 54,55 Therefore, the morphologies of the zinc deposits obtained at the edge and at the center region of the deposits in the electrolytes of 1.5 M ZnO/IL, 0.4 M Zn(TfO) 2 /IL and (0.4 M Zn(TfO) 2 + 1.5 M ZnO)/IL at −1.8 V for 2 h, respectively, were investigated by scanning electron microscopy (SEM). The images are shown in Fig.…”
Section: Morphology Of the Zinc Depositsmentioning
confidence: 99%
“…The shape of powder particles depends on both the conditions of electrolysis, such as the current density or overpotential, the type and composition of electrolyte, temperature, the type of working electrode, regime of electrolysis, etc., and the nature of metals [6]. Although powder particles are the most often dendritic shape, they can also be in the form of flakes, fibrous, spongy, wires at sub-micrometer or nanometer scale, cauliflower-like, as well as in the many other irregular forms [4][5][6][7][8][9][10][11][12][13][14][15][16]. Various forms of dendrites are formed by electrolysis, and the shape of dendritic particles is primarily determined by the type of metals [4,6,9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that edge roughness has a strong effect on the initiation time and propagation rate of dendrites ( Ref 7,8), no influence on the texture and morphology of dendrites was found in the evaluated range (not shown). Therefore, only the results for the samples G80 are presented in the following paragraphs.…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, in order to understand how the process variables influence dendritic growth during electrogalvanization, the rotating washer electrode (RWE) was designed: an electrochemical cell that replicates the fluid dynamics and the current distribution on the sheet edge. Several operating parameters were studied with the RWE in previous works (Ref 7,8); these results showed that electrolyte flow and current density have a great influence on the kinetics of dendrite growth. Nevertheless, the aforementioned research was focused on the formation of dendrites and little attention was paid to their morphology and texture.…”
Section: Introductionmentioning
confidence: 99%